Post exercise cardiovascular effects of different resistance exercise protocols for trunk and upper limbs - Annelise Lins Menêses (Motriz: Revista de Educacao Fisica, 2011)
Objective: to analyze the post exercise cardiovascular effects of different resistance exercise protocols for trunk and upper limbs. Methods: Fifteen males (22.3 ± 0.9 years) underwent three experimental sessions randomly: control session (C), resistance exercise session at 50% of one repetition maximum (1-RM) (E50%), and resistance exercise session at 70% of 1-RM (E70%). Three sets of 12, 9 and 6 repetitions were performed for each exercise. Blood pressure (BP), heart rate (HR) and rate pressure product (RPP) were measured before and during 90 minutes after each session. Results: Systolic BP decreased (P<.05) and diastolic BP increased (P<.05) similarly after C, E50% and E70%. However, HR and RPP decreased after C (P<.01), maintained after E50%, and increased after E70% (P<.01). Conclusions: The resistance exercise intensity did not influence post-exercise BP responses, however, cardiac overload was greater after E70%